Racializing Mestizos and Mestizas in the Philippines—Dean Worcester’s Anthropometric Types in the Early 20th Century - Sarah Albiez-Wieck (Histories, 2025)
In the Spanish Empire, the term mestizo/mestiza denoted, overwhelmingly, people of so-called “mixed” European and indigenous ancestry, but there existed also some regional adaptations with differing genealogies such as the mestizos de sangley in the Philippines. The article traces some developments of the application and racialization of the term mestizo shortly after the end of the Spanish Empire in the Philippines under U.S. rule. It will look at photographs that were taken in by Dean Worcester, secretary of the interior, and his staff, in order to apply and develop theories of the biologist racism, which in the early twentieth century was en vogue all over the globe. Worcester and his crew took the photographs during their expeditions and used them to illustrate their hypotheses about racialized taxonomies, adapting and further developing Spanish colonial ideas. I will contrast them with a photograph from a local studio in Mindanao. The photographs stem from the photographic collection of the Rautenstrauch-Joest Museum in Cologne, Germany.